Ultrasound-triggerennd piezocatalytic conductive Guar gum/PEDOT: PSS/BTO composite hydrogels for bacterial-infected skin wound healing - Shuyan Zhang; Danna Chen; Zhipeng Gu; Hongrong Luo; Xianchun Chen; Qiang Fu (Nano TransMed)
Open skin wounds are susceptible to infections by multidrug-resistant bacteria, which can lead to delayed wound healing or worsening of symptoms. Therefore, there is an urgent need to develop a comprehensive strategy that addresses bacterial infections while simultaneously promoting wound healing for optimal clinical outcomes. In this study, we aimed to combine the benefits of antibacterial piezoelectric catalysis action and controlled electrical stimulation to promote skin tissue repair. Initially, piezoelectric catalytic BaTiO3(BTO) nanoparticles were coated with polydopamine (PDA) to improve the interface compatibility between inorganic and organic phase. Subsequently, a novel conductive composite hydrogel termed PPGSCH was synthesized by doping PDA@BTO into poly (3, 4-ethylenedioxythiophene) -poly (styrene sulfonate) (PEDOT: PSS) hydrogel. Traditional dye degradation experiments and EPR tests found that PDA@BTO nanoparticles exhibited superior piezoelectric catalytic efficiency compared with the pristine BTO. Rheological tests and electrical conductivity tests demonstrated better electrical adaptability and mechanical stability of PPGSCH. Remarkably, under the synergism of piezoelectricity and electric polarization induced by ultrasound (US), the antibacterial rate of PPGSCH exceeded 90% in vitro. Furthermore, when subjected to 0.5 W/cm2 US irradiation, it can generate moderate levels of reactive oxygen (ROS) and micro current, promoting the proliferation and migration of mouse fibroblasts. Animal experiments on infected skin wounds in mice showed that PPGSCH could reduce inflammation, accelerate angiogenesis, and ultimately expedite the infected wound healing. This work opens up new possibilities for enhancing the repair of infected skin wounds.